2023
DOI: 10.1097/sap.0000000000003539
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Versus Delayed-Immediate Autologous Breast Reconstruction After Nipple-Sparing Mastectomy

Abstract: IntroductionAutologous reconstruction following nipple-sparing mastectomy (NSM) is either performed in a delayed-immediate fashion, with a tissue expander placed initially at the time of mastectomy and autologous reconstruction performed later, or immediately at the time of NSM. It has not been determined which method of reconstruction leads to more favorable patient outcomes and lower complication rates.MethodsWe performed a retrospective chart review of all patients who underwent autologous abdomen-based fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The Delayed-Immediate approach after ART is used to preserve the skin envelope using a TE ( 93 ). This two-stage approach has been successfully utilized in early-stage breast cancer (stage I and IIA) to perform an SSM/SNM, resulting in a smaller flap skin island, improved aesthetic outcomes, and reduced donor site morbidity ( 94 , 95 ). Although in locally advanced disease, the skin envelope cannot be saved due to the high risk of local recurrence, a protocol suggested by Kronowitz et al ( 96 ) demonstrated that delayed reconstruction with skin preservation could be indicated in IIB and III-stage breast cancer ( 96 ).…”
Section: Basic Concepts In Breast Reconstructionmentioning
confidence: 99%
“…The Delayed-Immediate approach after ART is used to preserve the skin envelope using a TE ( 93 ). This two-stage approach has been successfully utilized in early-stage breast cancer (stage I and IIA) to perform an SSM/SNM, resulting in a smaller flap skin island, improved aesthetic outcomes, and reduced donor site morbidity ( 94 , 95 ). Although in locally advanced disease, the skin envelope cannot be saved due to the high risk of local recurrence, a protocol suggested by Kronowitz et al ( 96 ) demonstrated that delayed reconstruction with skin preservation could be indicated in IIB and III-stage breast cancer ( 96 ).…”
Section: Basic Concepts In Breast Reconstructionmentioning
confidence: 99%